Essentials of food process engineering - Flores, Clifford
Food engineering is a multidisciplinary field of applied physical sciences which combines science, microbiology, and engineering education for food and related industries. Food engineering encompasses a wide range of activities. Food engineers are employed in food processing, food machinery, packaging, ingredient manufacturing, instrumentation, and control. This book covers the important topics which are extensively used in food process industry. The book also focuses on challenges to employ modern tools, technology, and knowledge in food processing.